(untitled) (Aporte Santiaguino, 2019)
Mexican public universities have placed special interest in achieving their objectives eciently; the above, becomes more relevant if the university is considered as an organization whose goals are non- nancial, so, it requires public resources to achieve its goals. The objective of this study is to estimate the factors that determine the productivity of public universities in the Southern region of Mexico during the period 2007 to 2017; for this,were used the inputs and outputs that make up the substantive functions of the universities, in the estimation the technique Data Envelopment Analysiswas used to determine theMalmquist Productivity Index of 8 public universities. The ndingswere that in the group of universities analyzed there is an increase in productivity, and that this is due to the improvement in the productive processes; likewise, universities act according to the principle of eciency. As conclusions we can point out, that the estimations by means of the Malmquist productivity Index allow to know the determining factors in the productivity of the studied units, and the size of the universities represents a fundamental element in the positive changes of the university productivity